Measuring patient satisfaction in sexually transmitted infection clinics: a systematic review. Issue 6 (13th October 2009) - Weston, R; Dabis, R; Ross, J D C
Abstract : Objectives: Measuring patient satisfaction is an important aspect of making services attractive to patients and improving service delivery, and outpatient-based clinics are increasingly assessing service quality using patient-based outcome measures. No systematic review of patient satisfaction in sexually transmitted infection clinics has previously been performed. The objectives of the review were: (1) to establish how patient satisfaction with sexual health services has been defined and measured; (2) to identify whether a "gold standard" method exists; and (3) to identify the themes regarded by patients as priorities for delivering a quality service within a sexually transmitted infection clinic setting. Methods: A search of eight electronic journal databases and unpublished data sources was used to identify studies measuring patient satisfaction in a sexually transmitted infection clinic setting. Following initial review of each abstract, data from eligible studies were extracted by two independent reviewers and content analysis used to identify common themes. Results: Eighteen questionnaire-based studies, nine semistructured interviews and four other studies, including three focus groups, fulfilled the selection criteria for inclusion. Three studies incorporated more than one method of analysis. No common validated method of assessing patient satisfaction was identified. Themes reported to be of greatest importance were the convenience of clinic location, availability of appointments, staff attitude to patients, effective provision of information and maintenance of confidentiality. Conclusions: This review has identified the need for a validated and standardised approach to assess patient satisfaction in sexually transmitted infection clinics. Comparing studies which have measured satisfaction, clear themes for the provision of a high quality service, from a patient perspective, have emerged. These themes should be incorporated into assessment tools, such as questionnaires, when reviewing service delivery.